From Chaos to Strength: Socio-Labor Aspects as Catalysts of Resilience in Times of University Crisis - Montano, Julio; Alcahuaman, Jeny; Montano, Santos (Journal of Ecohumanism, 2025)
In Peru, the National Superintendence of Higher University Education (SUNEDU), when establishing licensing guidelines, left out several institutions, generating uncertainty and affecting administrative staff. In order to analyze the influence of socio-labor aspects on the resilience of those who work in a private, unlicensed university, a quantitative approach, a non-experimental design, and an explanatory correlational scope were used. The population, composed of 51 administrative workers, was evaluated using validated instruments, covering dimensions of bond of belonging, social integration, and solidarity, as well as the adaptive capacity, emotional support, and self-efficacy. The results show positive and significant correlations between socio-labor aspects and resilience (Rho between 0.678 and 0.822), with socio-labor aspects explaining 62.9% of the variability of resilience, and showing that management focused on strengthening the sense of community and collaboration can contribute to greater collective well-being and better organizational adaptation.